Condiciones para un desarrollo sustentable de sistemas de trabajo en los países emergentes: El caso de tres empresas en Túnez - Tahar-Hakim Benchekroun; Raouf Ghram; Catherine Fournier; Francis Six; Mohamed Akrout (Universidade do Porto, 2009)
During the globalization of the economy and of the financial exchanges, the so-called "emergent" countries have seen companies and job rates increasing. Anthropotechnological studies have shown failures in many technology transfers from countries of the "North" towards countries of the "South" during the 80´s and the 90´s. What is the current state of these movements today? Moreover, do the relocations bring new stakes and processes similar to these technology transfers? These evolutions impacted directly on the companies' structure and organization, producing different development levels concerning the scope of the management when compared with the organization and execution domains. The "success" of the upgrade on the finance world, the marketing and the management, according to current criteria in developed countries, contrasts with the world of the production and the execution that continues to face contrasting situations in terms of technical and organizational reliability and precarious working conditions with important risks for health, safety, job precariousness and expertise development. To act on the imbalances between these two spheres that coexist without working together and that "split" the companies in two distinct and distant parts, therefore constitutes one of the major stakes in the sustainable development of work systems.